Association between alcohol drinking frequency and depression among adults in the United States: a cross-sectional study - Peng Qi; Mengjie Huang; Haiyan Zhu (BMC Psychiatry)
Abstract Background Depression is a major contributor to the global burden of diseases, and alcohol intake is often considered to be associated with depression. However, the relationship between alcohol drinking frequency and depression remains unclear. This study aims to explore the association between alcohol drinking frequency and depression. Methods This study collected NHANES data from 2009 to 2016, involving 17,466 participants. Depression was diagnosed based on the Patient Health Questionnaire-9 (PHQ-9), and alcohol drinking frequency was collected through questionnaire surveys. Multifactorial logistic regression models, subgroup analysis, smooth curve fitting, and threshold effect analysis were used to investigate the relationship between alcohol drinking frequency and depression. Results We divided the alcohol drinking frequency into five groups on average. After adjusting for all covariates, the Q3 group had the lowest odds of depression (OR = 0.68; 95% CI: 0.56 ~ 0.82; p < 0.05). Through smooth curve fitting, we found an “M-shaped” relationship between alcohol drinking frequency and depression. Further threshold effect analysis revealed that the most significant inflection points were 80 and 150. Conclusion In this cross-sectional study of American adults, we found an “M-shaped” relationship between alcohol drinking frequency and depression, which may partially explain the different effects of moderate alcohol consumption on depression.